An Interdisciplinary Approach to Understanding the Psychological Impact of Different Grammaticalizations of the Future. Issue 1 (7th May 2020) - Jäggi, Tiziana; Sato, Sayaka; Gillioz, Christelle; Gygax, Pascal Mark
Considering how fundamental and ubiquitous temporal information is in discourse (e.g., Zwaan & Radvansky, 1998 ), it seems rather surprising that the impact of the grammaticalization of the future on the way we perceive the future has only been scarcely studied. We argue that this may be due to its rather abstract nature and how it has been previously operationalized. In this review, we lay the foundation for studying the impact of the grammaticalization of the future on mental representations of the future by taking an interdisciplinary perspective, connecting cognitive sciences, linguistics, psycholinguistics, economics, and health psychology. More specifically, we argue that experimental psycholinguistics, combined with more applied domains, constitute a promising research avenue.